TRANSFORMASI DIGITAL UMKM RITEL: EDUKASI SISTEM INFORMASI AKUNTANSI DAN PENGGUNAAN TEKNOLOGI ERP DI MINIMARKET MALIKA - Defitri, Siska Yulia; Hikmah, Vinka Tahiyatul Nurul; Putri, Afchellya Anugrah; Amril, Zahara Putriani; Rahmatullah, Jabil; Sukraini, Juita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service initiative addresses the limited understanding of accounting information systems and digital technology use among retail MSME actors, particularly Enterprise Resource Planning (ERP). The activity aims to improve digital literacy and business management through education and hands-on training in a partner minimarket. The method includes outreach and assistance in implementing cloud-based ERP software. The results show improved participant skills in recording transactions and managing business data integratively. This program is expected to accelerate the digital transformation of retail MSMEs and enhance their competitiveness in the digital economy.